Economic costs, impacts and financing strategies for mental health in South Africa - Docrat, Sumaiyah (Department of Psychiatry and Mental Health, 2020)
Over the past decade, calls to address the increasing burden of mental, neurological and substance-use (MNS) disorders and to include mental health care as an essential component of universal health coverage (UHC) have attracted mounting interest from governments. With the inclusion of mental health in the 2015 Sustainable Development Goals (SDGs) there is now a global policy commitment to invest in mental health as a health, humanitarian and development priority. Low and middle-income countries (LMICs) such as South Africa, contemplating mental health system scale-up embedded into wider SDG- and UHC-related health-sector transformations, must address a number of key mental health financing policy considerations for attaining population-based improvements in mental health. Despite ongoing transformations in the South African health sector, there has been an implicit neglect of the integration of mental health services into general health service development. This has been driven in part by a lack of locally-derived evidence in several areas, including: the economic basis for investing in mental health, the current resourcing of the mental health system, opportunities for improved efficiency and equity, and how reforms may be structured and paid for in light of the country's ongoing efforts to implement a National Health Insurance (NHI) scheme. This thesis therefore attempts to address these gaps and aims to generate new knowledge on the economic costs, impacts and financing strategies for mental health in South Africa. This aim is achieved by fulfilling the following research objectives: 1. To examine the impact of social, national and community-based health insurance on health care utilization for MNS disorders in low- and middle-income countries. 2. To examine the policy context, strategic needs, barriers and opportunities for sustainable financing for mental health in South Africa. 3. To quantify public health system expenditure on mental health services, by service level and province, and to document and evaluate the resources and constraints of the mental health system in South Africa. 4. To examine the household economic costs and levels of financial risk protection associated with depression symptoms in South Africa. In the first part, the systematic review reports on the impact of social, national and community based health insurance on health care utilization for MNS disorders in LMICs, published until October 2018. As a secondary goal, the systematic review identifies whether there are any specific lessons that can be learnt from existing approaches to integrate mental health care into financing reforms towards universal health coverage. In the second part, a qualitative examination of the policy context, strategic needs, barriers and opportunities for sustainable financing for mental health in South Africa was conducted through a situational analysis that was complimented with a synthesis of key stakeholder consultations. The findings provide recommendations for how scaled-up mental health services can best be paid for in a way that is feasible, fair and appropriate within the fiscal constraints and structures of the country. In the third part, the thesis then empirically quantified public health system expenditure on mental health services, by service-level and province for the 2016/17 financial year, and documented and evaluated the resources and constraints of existing mental health investments in South Africa through a national survey; achieving one of the highest sample sizes of any costing study conducted for mental health in LMICs. In the fourth and final part, a household survey study was conducted to determine the level of financial protection for persons living with depression symptoms in the Dr. Kenneth Kaunda health district of South Africa, which is serving as a pilot site for the NHI. The household economic factors associated with increased depression symptom severity on a continuum are reported; and demonstrate that financial risk protection efforts are needed across this continuum. The thesis concludes by synthesizing findings towards an improved understanding of the key lessons that can be learned from other LMICs toward sustainable financing for mental health; the economic burden of inadequate mental health care to households in South Africa; and the efficiency of existing mental health investments and inequities in resourcing and access. Through this lens, and borrowing from the experiences of other LMICs, recommendations for key priorities for health service and financing reforms towards the scaled-up delivery of mental health services in South Africa are generated. The thesis is presented as papers embedded in a narrative that includes an introduction and synthesis discussion. Four papers (3 published and 1 under review) form the basis of the results chapters.